Kebijakan Industri Menghadapi Globalisasi - Mila Azizah; M. Zikri Hidayat; Ristiana Hidayah; Rina Astuti; Naerul Edwin Kiky Aprianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Industrial policy in Indonesia faces significant challenges in an era of increasingly complex globalization. Globalization brings great opportunities for domestic companies to compete globally, but also poses risks such as economic inequality and unemployment. To address these challenges, the government needs to develop a smart industrial policy that not only encourages sectoral growth but also stimulates cross-sectoral innovation. Selecting imported goods, imposing high import fees on commodities that can already be produced domestically, and providing capital injections to companies with comparative advantages are effective ways to protect local industries from the negative impacts of globalization. Digitalization must also go hand in hand with the implementation of this strategy so that sectors can use digital technology to increase productivity and create new economic opportunities, especially for micro, small, and start-up businesses. Furthermore, Indonesia's economic strength in navigating the problems of globalization may lie in its integration with the creative economy. Indonesia's industrial economy requires creative and innovative human resources so that the creative sector can develop and compete on a global scale.